Pricing Strategy, Financial Knowledge, And Risk Perception:Determining Factors In The Decision To Use Online Loan Services - Fitriyah, Zumrotul; Raharjo, Raden Johnny Hadi (UNIVERSITAS PAKUAN, 2025)
This research explores how pricing strategies, financial literacy, and risk perceptions influence decisions to utilize online loan services, with a focus on online satisfaction as an intermediary factor. The study aims to pinpoint key determinants affecting the acceptance of online lending platforms in Indonesia. Employing a quantitative method, data were collected from a sample of 100 individuals who have previously used such services. The findings indicate that pricing, financial knowledge, and risk perception significantly influence users' decisions to engage with online lending. Moreover, the role of online satisfaction as a mediating variable was confirmed. This research adds to existing literature by offering a deeper understanding of consumer behavior in the fintech lending sector in Indonesia, providing valuable insights for policymakers and industry professionals to enhance the uptake of online loan services in the region